Psychological Distress in Emerging Adulthood Following Parental Death: How Do Resilience and Social Support Contribute? - Pinis, Eunike Margaritha; Rahayu, Maria Nugraheni Mardi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The death of a parent during emerging adulthood is an emotionally challenging experience that can lead to a high level of psychological distress. This study examines the roles of resilience and social support in predicting psychological distress among emerging adults who have experienced parental loss. Participants were 100 individuals aged 18–25 years who had lost one of their parents. The instruments used were Depression, Anxiety, and Stress Scale-21 (DASS-21), the Connor-Davidson Resilience Scale (CD-RISC), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using multiple linear regression. The results indicated that: (1) resilience significantly contributes to psychological distress among emerging adults who have lost a parent; (2) social support does not play a significant role in psychological distress in this context; and (3) when examined together, resilience and social support do not have a combined significant effect on psychological distress. These findings highlight the importance of fostering resilience as a protective buffer for emerging adults coping with the death of a parent.Kematian salah satu orang tua pada masa dewasa awal merupakan pengalaman emosional yang berat dan berpotensi menimbulkan distres psikologis yang tinggi. Penelitian ini bertujuan untuk mengetahui peran resiliensi dan dukungan sosial terhadap distres psikologis pada individu dewasa awal yang menghadapi kematian salah satu orang tua. Partisipan dalam penelitian ini berjumlah 100 individu berusia 18 – 25 tahun yang telah kehilangan salah satu orang tua akibat kematian. Alat ukur yang digunakan dalam penelitian ini adalah Depression, Anxiety, Stress Scale-21 (DASS-21), Connor-Davidson Resilience Scale (CD-RISC), Multidimensional Scale of Perceived Social Support (MSPSS). Teknik analisis data yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Berdasarkan hasil analisis regresi berganda diperoleh kesimpulan bahwa 1) terdapat peran resiliensi terhadap distres psikologis individu dewasa awal yang menghadapi kematian salah satu orang tua; 2) tidak terdapat peran dukungan sosial terhadap distres psikologis individu dewasa awal yang menghadapi kematian salah satu orang tua; 3) tidak terdapat peran resiliensi dan dukungan sosial terhadap distres psikologis individu dewasa awal yang menghadapi kematian salah satu orang tua. Penelitian ini menunjukkan pentingnya pengembangan resiliensi sebagai penyangga pelindung bagi individu dewasa awal yang menghadapi kematian salah satu orang tua.